Understanding adolescent cyberbullying: The mediating role of problematic internet use in the associations between self-control, parental monitoring and cyberbullying - Andik Matulessy; Nurussakinah Daulay; Prakash Padakannaya; Mamang Efendy; Muhammad Irfan Nazieh (Psikohumaniora: Jurnal Penelitian Psikologi, 2026)
Social media provides adolescents with opportunities for self-expression, but it also increases the risk of cyberbullying. This study examines the direct relationship between self-control and parental monitoring and cyberbullying, and investigates whether problematic internet use mediates the relationships. The study involved 2.517 secondary school students (M-age = 16.40; SD = 1.08) who were recruited through convenience sampling. Data were collected online using four scales: a Cyberbullying Scale, the Problematic Internet Use Scale, a Parental Monitoring Scale, and a Self-control Scale. Data were analyzed using path analysis with Jamovi software. The results show that problematic internet use mediated the effects of self-control (β = −.035, p < .001) and parental monitoring (β = −.029, p < .001) on cyberbullying. The findings highlight the need for integrated prevention strategies to strengthen adolescents’ self-regulation, supportive parental monitoring, and healthy internet use through collaboration between schools, families, and communities.